npj Climate and Atmospheric Science - Harrison, Roy.; Kucharski, Fred.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Climate and Atmospheric Science considers research that explores all aspects of the physical, chemical and biological components of the climate and atmospheric sciences. The journal covers a broad range of topics including but not limited to: Climate dynamics and variability Weather forecasting and climate prediction Climate change and paleoclimate, including Cryosphere Ocean dynamics Dynamical Meteorology Weather extremes Air pollution Atmospheric chemistry and physics, including aerosols The hydrological cycle and atmosphere-ocean and atmosphere-land interactions, including vegetation Use of advanced numerical methods, such as machine learning and artificial intelligence applied to weather, climate, and air quality prediction The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by climate and atmospheric science experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Earth sciences; Climatology; Atmospheric science; Pollution; Earth Sciences; Climate Sciences; Atmospheric Science; Pollution